Haha popi faces of Chinoy Catholics today - Go, Johnny; Gancia, Carol; Pe, Ampi T. (Quezon City Jesuit Communications, 2000)
A documentary on Chinese Filipino Catholics and how they deal with ethnic identity, faith, and culture.
A Jesuit Communications production in cooperation with the Jesuit Province Commission on Chinese Filipino Ministry.
Includes a companion guide for facilitators.
VHS.
Keywords: Sociology; Anthropology